Operação do gerador de indução em conexão assíncrona com a rede monofásica - LIMA, Nelio Neves (2010)
This text reports the effort to present a proposal of a power generation system based on cage rotor Induction Electrical Machine associated to a sinusoidally-switched PWM (Pulse Width Modulation) frequency converter responsible for maintaining constant 60 Hz frequency at the generator leads. DC side at the PWM converter is nonsynchronously connected to a single-phase utility line by means of a full-bridge current-fed thyristor inverter, employing a step-down DC-DC converter in order to turn the grid injected current into a sinusoidal waveform. The proposed system allows for the operation as cogenerator in sites fed by single-phase utility net where there is availability of energetic resources. The DC capacitor voltage (Vdc) is controlled through the DC side energy balance adjusting the amplitude of the active current sent to the utility grid. The control strategy employed was the analogic proportional-integral (PI) error compensation. The system is also able to act as reactive power compensator to the AC loads as the Cdc capacitor represents a voltage source to the inverter and the three-phase diode bridge allows for bidirectional power flow between AC and DC sides. Simulation and experimental results has corroborated system viability to provide three-phase balanced regulated voltages complying with ANEEL 505/2001 Resolution and with IEEE Std 519-1992.